Serologic Survey of Selected Viral Pathogens in Free-Ranging Eurasian Brown Bears ( Ursus arctos arctos) from Slovakia - Vitásková, Eliška; Molnár, Ladislav; Holko, Ivan; Supuka, Peter; Černíková, Lenka; Bártová, Eva; Sedlák, Kamil (Journal of wildlife diseases, 2019)
We tested sera of 24 free-ranging European brown bears ( Ursus arctos) from six regions of Slovakia for antibodies to 10 viral agents. We tested sera by an indirect fluorescence antibody test for antibodies to canine distemper virus (CDV), canine coronavirus (CCV), canine parvovirus type 2 (CPV-2), canine adenovirus, canine parainfluenza virus type 2 (CPIV-2), and canine herpesvirus type 1 (CHV-1). We used an enzyme-linked immunosorbent assay for detection of antibodies to hepatitis E virus, bluetongue virus, West Nile virus (WNV), and Aujeszky's disease virus (ADV). We detected antibodies to CDV, CHV-1, CPV-2, CPIV-2, CCV, WNV, and ADV in seven (29%), three (12%), two (8%), two (8%), one (4%), one (4%), and one (4%) bear, respectively. Evidence of exposure of free-ranging European brown bears to CCV and ADV has not been reported.
Keywords: coronavirus; West Nile virus; Virus Diseases; séroepidemiologické studie; Ursidae; virové nemoci; Aujeszky's disease virus; zvířata; Slovakia; Slovenská republika; herpesvirus; parvovirus; medvědovití; protilátky virové; Antibodies, Viral; Animals; distemper virus; parainfluenza; Seroepidemiologic Studies